Daya hasil genotipe jagung merah Unipa pada beberapa ame-lioran di Distrik Manokwari Utara - Lenda Mawikere, Nouke; Kilala, Ary; Ilona Noya, Alce; S. Sarungallo, Amelia; Purbokurniawan; Abbas, Barahima (Program Pascasarjana Universitas Papua, 2024)
ABSTRACT: This research aims to find out the types of ameliorant and the local West Papua genotypes that have the best influence on corn productivity, identify the yield of several promoting genotypes of the local West Papua red corn using several types of ameliorant in North Manokwari District, and know the right type of the ameliorant for increasing the yield of several promoting genotype of the local West Papua red corn. The study used a split-plot design with the combination treatments of ameliorant types and corn plant genotypes. The types of ameliorant as the first treatment factor which was allocated as a main plot consisted of Control or without ameliorant (Ao), Chicken Manure (A1), and Goat Manure (A2). The second factor (G) as a subplot consisted of 8 types of corn genotypes (AMP-UNIPA 1, AMP-UNIPA 2, AMP-UNIPA 3, AMP-UNIPA 4, AMP-UNIPA 5, AMP-UNIPA 6, AMP-UNIPA 7, and AML-UNIPA (local varieties). The results showed that the combination of ameliorant and corn genotypes treatments produced a different influence on the growth and yield components of corn. Several important variables in the growth component as well as the corn yield component showed the best results as an influence of goat manure ameliorant application.